The analysis of slip tendency of major tectonic faults in Germany - L. Röckel; S. Ahlers; B. Müller; K. Reiter; O. Heidbach; O. Heidbach; A. Henk; T. Hergert; F. Schilling (Solid Earth, 2022)
Seismic hazard during subsurface operations is often related to the reactivation of pre-existing tectonic faults. The analysis of the slip tendency, i.e., the ratio of shear to normal stress acting on the fault plane, allows an assessment of the reactivation potential of faults. We use the total stresses that result from a large-scale 3D geomechanical–numerical model of Germany and adjacent areas to calculate the slip tendency for three 3D fault geometry sets with increasing complexity. This allows us to draw general conclusions about the influence of the fault geometry on the reactivation potential.